Delays in healthcare consultations about obesity — Barriers and implications. Issue 5 (September 2020) - Rigas, Georgia; Williams, Kathryn; Sumithran, Priya; Brown, Wendy A.; Swinbourne, Jessica; Purcell, Katrina; Caterson, Ian D.
Highlights: Obesity remains greatly underdiagnosed and undertreated. PwO are motivated to lose weight which offers an opportunity for HCPs to initiate earlier weight discussions/consultations. PwO would like their HCP to initiate a conversation about weight. Better recognition of obesity's impact and targeting barriers to care are needed. Improvement in and earlier access to obesity care are required. Abstract: Background: The prevalence of obesity continues to rise, affecting nearly a third of Australian adults in 2017–18. The stigma and bias people with obesity (PwO) experience is one of the barriers hindering the dialogue between PwO and their Health Care Professionals (HCPs). The results from the ACTION IO Australian cohort are reported here. Identification of local barriers can inform strategies to improve access to quality obesity care within Australia. Methods: The ACTION-IO study was an online cross-sectional survey conducted in 11 countries during June–October 2018. In Australia 1, 000 community based adult PwO (body mass index ≥30 kg/m based on self-reported height and weight) and 200 HCPs involved with direct patient care (seeing ≥10 patients with obesity/month) completed the survey. Results: There was a mean delay of 8.9 years from when a PwO first started to struggle with their weight, and the initial discussion with an HCP about this. HCPs acknowledged weight loss efforts in only 38.5% of their patients, although 74.6% of PwO had attempted weight loss. Most PwO (82.0%) assumed full responsibility for their weight loss. HCPs identified short appointment times (60.5%) and the cost of obesity medication, programmes and services (58.5%) as barriers to weight management conversations and weight loss, respectively. Most PwO want their HCP to raise the issue of weight with 64 % reporting finding such conversations positive and helpful. Conclusion: Compared to global results, Australian PwO took 3 years longer to seek medical care about their weight. Better recognition of obesity's impact and targeting barriers to care are needed.